2020
DOI: 10.1108/tqm-04-2019-0107
|View full text |Cite
|
Sign up to set email alerts
|

The role of risk management in buyer-supplier relationships with a preferred customer status for total quality management

Abstract: PurposeThis paper provides a comprehensive risk management framework for buyer-supplier relationships where the buyer has the status of a preferred customer with the supplier.Design/methodology/approachEmpirical evidence is offered with a case study on a large multinational organization in the Fast Moving Consumer Goods (FMCG) industry, with some real-life perspectives on the main risks, mitigation strategies, and issues faced when applying the risk management framework.FindingsThe results show that several ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 79 publications
(99 reference statements)
0
11
0
Order By: Relevance
“…Supplier management: Relationships with suppliers have been discussed in the soft TQM literature, which has often questioned the necessity of implementing a specific system to control processes and relational exchanges to ensure the success of a project (Pellegrino et al, 2020;Sriyakul et al, 2019). Eventually, if it is impossible to adopt these protocols within social care organizations, specific human resources could be allocated to perform such tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Supplier management: Relationships with suppliers have been discussed in the soft TQM literature, which has often questioned the necessity of implementing a specific system to control processes and relational exchanges to ensure the success of a project (Pellegrino et al, 2020;Sriyakul et al, 2019). Eventually, if it is impossible to adopt these protocols within social care organizations, specific human resources could be allocated to perform such tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the operation, there is a continuous effort focused on quality areas (Pellegrino, Costantino, & Tauro, 2020). The concept of quality-oriented towards customer satisfaction in an integrated manner and reasonable quality costs should be established as one of the primary objectives.…”
mentioning
confidence: 99%
“…Their hypothesis confirms that customer attraction and supplier satisfaction are two different concepts which can influence the behaviour of suppliers in different ways. Pellegrino et al (2020) provided in their research a framework regarding risk management for buyer-supplier relationships where the buying firm has the preferred Chapter 1: Thesis background and research structure customer status with the supplier. Contributing to the study of Pulles et al (2016a), their research showed that customer attractiveness and supplier satisfaction are different concepts and "should be treated as distinctive variables with diverse roles in relationships with a preferred customer" (Pellegrino et al, 2020, p. 975).…”
Section: Praxmarermentioning
confidence: 99%
“…A preferred customer receives special treatment from its supplier, such as a collaborative development or allocation of its best personnel, thereby gaining competitive advantages over its competitor (Pulles et al, 2016a). Preferential resource allocation implies a stronger buyer-supplier relationship (Glas, 2018;Pellegrino et al, 2020). Consequently, satisfaction has been argued to be necessary to achieve preferential resource allocation by a supplier (Schiele et al, 2012).…”
Section: Preferential Resource Allocation Through Supplier Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation